Keterlibatan Anggota Keluarga Dalam Bisnis Dan Hubungannya Terhadap Kinerja Bisnis UMKM di Kota Padang - Riri Farastika; Firman Firman (Universitas Negeri Padang, 2019)
Purpose - This study aims to determine the relationship of family member involvement in business to the performance of SMEs businesses in the city of Padang.Methodology - The population in this study were allSMEs in the city of Padang. The sampling technique in this study is Non Probability Sampling. The number of samples is 100 respondents. The data analysis technique used is descriptive statistical analysis in the form of frequency distribution, percentage, cross tabulation, and chi-square test.Finding - From the results of this study, it can be seen that there is no significant relationship between the involvement of family members in the business towards the business performance of SMEs in Padang City. However, there is a significant relationship between the involvement of the number of family members and the dimensions of business performance, namely financial performance, the position of female family members significantly related to the dimensions of business performance, namely financial performance and preparing for the future. , the source of personal / friends' personal capital is significantly related to the dimensions of business performance, namely people development, the last source of bank capital is significantly related to the dimensions of business performance, namely financial performance.Keyword : Family member involvement, Business performance, family business